2016
DOI: 10.1016/j.cell.2016.03.023
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Cell RNA-Seq Reveals Lineage and X Chromosome Dynamics in Human Preimplantation Embryos

Abstract: SummaryMouse studies have been instrumental in forming our current understanding of early cell-lineage decisions; however, similar insights into the early human development are severely limited. Here, we present a comprehensive transcriptional map of human embryo development, including the sequenced transcriptomes of 1,529 individual cells from 88 human preimplantation embryos. These data show that cells undergo an intermediate state of co-expression of lineage-specific genes, followed by a concurrent establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

82
1,313
5
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 886 publications
(1,404 citation statements)
references
References 45 publications
82
1,313
5
4
Order By: Relevance
“…DEg-up genes of E3 also are enriched in CC GO terms of nucleus and nucleoplasm. These GO terms are consistent with the process of zygotic genome activation (ZGA) or embryonic genome activation (EGA) that occurs at E3 (36,45), which brings the burst of transcription (55) in nucleus (56,57) simultaneously ( Figure 4B). …”
Section: Performances On the Simulation Datasupporting
confidence: 53%
See 2 more Smart Citations
“…DEg-up genes of E3 also are enriched in CC GO terms of nucleus and nucleoplasm. These GO terms are consistent with the process of zygotic genome activation (ZGA) or embryonic genome activation (EGA) that occurs at E3 (36,45), which brings the burst of transcription (55) in nucleus (56,57) simultaneously ( Figure 4B). …”
Section: Performances On the Simulation Datasupporting
confidence: 53%
“…According to the recent study of Petropoulos et al (36), human preimplantation embryonic cells will differentiate into three lineages of epiblast (EPI), primitive endoderm (PE) and trophectoderm (TE) simultaneously at E5. And Rasmussen et al showed that collagen could improve the differentiation of human embryonic cells towards endoderm (54), which implies some inner cells of morula will synthesize collagen at E4 to induce themselves to differentiate into PE cells at E5.…”
Section: Performances On the Simulation Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This capability has allowed researchers to address exciting questions ranging from the response of single immune cells to antigen (4)(5)(6) to the number of transcriptionally distinct cell types and the cellular heterogeneity within complex tissues (7)(8)(9)(10)(11)(12)(13). Recent advances in the automated handling of individual cells and the sequencing library preparation for these cells have substantially increased the number of cells that can be routinely characterized with these approaches; notably, state-of-the-art droplet-based RNA-seq approaches provide the ability to quantify the transcriptome of tens of thousands or more cells (14,15).…”
mentioning
confidence: 99%
“…One article published last year suggests that XIST expression in human blastocysts may play a role in dampening X-chromosome expression, i.e., reducing the expression of both X chromosomes rather than inactivating one of them. The analysis of the transcriptome during human preimplantation development by RNAseq in single blastomeres revealed that both X-chromosome remain active throughout the whole period, as biallelic expression was maintained (10). However, they observed a progressive dampening of both X-chromosomes as (I) the sex-specific differences on the transcription of X-linked genes are gradually reduced; and (II) there is a female-specific progressive downregulation of X-linked genes.…”
Section: Editorialmentioning
confidence: 99%